Expressão de MMP-2 e MMP-9 no endométrio de éguas saudáveis e portadoras de endometrite crônica - Porto, C. D.; Nunes, L. C. [UNESP]; Masseno, A. P. B. [UNESP]; Sequeira, Julio Lopes [UNESP]; Oliveira, D. E. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
Avaliaram-se, por método imunoistoquímico, a expressão e distribuição das metaloproteinases (MMP) 2 e 9 em amostras de endométrio hígido e de éguas portadoras de endometrite crônica. Foram utilizadas 60 biópsias endometriais. A MMP-2 foi observada na parede vascular, nas células estromais e no epitélio glandular, e a imunorreatividade mais intensa foi obtida nas células do epitélio glandular nas endometrites da categoria III e na parede vascular nos endométrios da categoria I. A marcação imunoistoquímica para MMP-9 mostrou-se difusa pelo endométrio e foi observada no epitélio luminal e glandular, na região da parede vascular, nas células estromais, endoteliais e do infiltrado inflamatório. Houve diminuição da marcação imunoistoquímica na região da parede vascular conforme aumentou o grau das lesões endometriais concomitante à diminuição da intensidade da reação. Não houve relação na expressão imunoistoquímica das metaloproteinases estudadas com o tipo de endometrite

The expression and distribution of matrix metalloproteinases (MMP) 2 and 9 were evaluated in helth endometrium and in chronic endometrites of mares by means of immunohistochemistry method. Sixty endometrial biopsies were utilized. Expression of MMP-2 was observed in vascular wall, stromal cells, and glandular epithelium. More intense immune reaction was seen in glandular epithelial cells in category III endometritis and in vascular wall in category I endometrium. MMP-9 immune reaction was diffuse and was seen in luminal and glandular epithelium; vascular wall region; and stromal, endotelial, and inflammatory cells. There was a decreased of the immunohistochemical marking in vascular wall region as increased the degree of endometrial injury, as well as reducing the intensity of reaction in this compartment. There was no relation in immunohistochemistry expression of metalloproteinases with the type of endometritis
Expression of MMP-2 and MMP-9 in helth endometrium and in chronic endometritis of mares
Keywords: equino; endométrio; inflamação; fibrose; metaloproteinase; equine; endometrium; inflammation; fibrosis; metalloproteinases